Pengaruh Green Marketing Dan Brand Equity Terhadap Purchase Intention Air Minum Dalam Kemasan Merek Aqua (Studi Pada Masyarakat Di Kabupaten Jombang) - Vindi Nur Maharani; Muhyidin Zainul Arifin; Mar’atul Fahimah (Universitas KH. A. Wahab Hasbullah, 2019)
ABSTRACT This research discusses the influence of green marketing and brand equity on purchase intention bottled drinking water brand AQUA in society Jombang. The purpose of this research to determine whether there is a correlation between green marketing and brand equity with purchase intention bottled drinking water brand AQUA in Jombang City. The results of hypothesis testing partial and simultaneously show that green marketing and brand equity is influence purchase intention bottled drinking water brand AQUA. It’s mean that, if the value of green marketing and brand equity down/up so purchase intention bottled drinking water brand AQUA will decrease/increase. The correlation between green marketing, brand equity, and purchase intention is moderate, so the company need for product innovation, improve product quality, distribution, marketing, and other operational activities to increase purchase intention.